Channel Modelling for V2V Highway Scenario Based on Birth and Death Process. (14th March 2022) - Feng, Yi; Ge, Ning; Tao, Xiaoming; Song, Qiwei; Xiang, Tao
Abstract : Vehicle-to-vehicle (V2V) communication has been widely researched recently since the potential abilities of improving traffic efficiency and reducing accident rates. Since the high vehicle mobility, a huge number of accidents happen on highway. So, it is necessary to study the highway channel characteristic to ensure the driving safety. Due to the high speed of vehicles, there exists serious nonstationarity of highway channel, leading to the dissatisfaction of the wide-scene stationary uncorrelated scattering (WSSUS) assumption. Thus, a distant channel model is needed. In this paper, we carried out a measurement campaign of highway channel. Based on the measured data, we conduct a birth and death channel model, which is depicted by Markov chain. We propose the first-order model and the second-order model, respectively. The steady probabilities and transition probabilities are given. To compare the two models, we utilize the multipath living time and Kullback-Leibler (KL) distance. What is more, autocorrelation function (ACF) is used to describe the nonstationarity.